Deriving the skyrmion Hall angle from skyrmion lattice dynamics - R. Brearton (Nature Portfolio, 2021)
Skyrmions, when driven by any applied force, experience an addition sideways motion known as the skyrmion hall effect. Here, Brearton et al. present a reciprocal space method for determining the strength of the skyrmion hall effect, making measurement possible for skyrmion lattices.